Morphological variations of Phrosina semilunata Risso, 1822 juveniles (Crustacea: Amphipoda: Hyperiidea), new evidence from the Gulf of Mexico - Violante-Huerta, Marco; Sanvicente-Añorve, Laura; Hermoso-Salazar, Margarita; Marrón-Becerra, Aurora (Zootaxa, 2021)
Lack of knowledge of morphological variations during growth of amphipod crustaceans can result in misidentification of species. In this study, we advance the knowledge of morphological variations of juveniles of the monotypic genus Phrosina Risso, 1822 collected in the oceanic province of the southern Gulf of Mexico. The juveniles differed from the adults mainly in the morphology of pereopods 3 & 4 in that the carpal process is parallel to the propodus, also the rami of the pleopoda consist of only four segments, uropoda 3 are more lanceolate, and the uropoda bear a large prominent spine terminally. These morphological variations have not been described for the species previously. Therefore, the current observations enrich the description of P. semilunata in the early stages of growth and support the need for further taxonomical studiest that could help identify species at different stages of development.